Blended Learning in Teaching Language for Occupational Purposes: Flexible E-textbook Design - Elena Alexeeva; Svetlana Buriakova (ARPHA Proceedings, 2021)
The article analyses the experience of developing an adaptive electronic textbook of French for occupational purposes for the MA programme "Linguistic support of project activities in the field of international cooperation". The authors substantiate the use of the genre-based approach, project-based learning, "flipped classroom" technique and gamification of learning in the design of educational scenarios which can be successfully implemented in the format of traditional, blended and distance learning. In addition, the developed content can be presented via a ready-made virtual educational environment, for example, Moodle, or using a system of disparate blended and distance learning tools. Taking into consideration that the lack of access to equipment and technologies is one of the major risk factors in distance learning introduced in connection with the Covid-19 pandemic, the authors provide a list of tools, depending on their pedagogical function, to be used for implementing designed learning scenarios in various educational contexts. The experience of designing an adaptive electronic textbook and literature review allowed to bring some clarifications in the definition of an e-textbook. It can be considered as a system of teaching content, exercises and tasks, educational scenarios, as well as descriptions of the pedagogical functions of the tools necessary for their implementation. The choice of specific tools that perform one or another pedagogical function should remain with the teacher, depending on concrete educational context.